A Proposed Framework for ERP System Implementation in SMEs - Setiawan, Danang; Fahrezha, Muhammad; Prakoso, Nur Abdillah Bagus; Qurtubi, Qurtubi (Universitas Dharma Wacana, 2023)
SMEs face numerous challenges and opportunities due to their pivotal roles in the economic development of a country. Adopting an ERP system is believed to be the catalyst to cope with the challenges and grab the opportunities faced by SMEs. However, implementing ERP led to potential risks caused by implementation failure, even for big companies. SMEs have a unique characteristic due to being receptive to adopting new technologies but having limited resources. Most previous research related to designing frameworks for ERP implementation was focused on big companies, although the fact that SMEs have distinct characteristics compared to big companies. Therefore, this study aims to design a framework for SMEs' ERP implementation. The framework phase consists of (1) measuring the business maturity, information communication and technology (ICT) maturity, proposed business process improvement, and (2) implementing an ERP system. The author has also provided a case study of ERP adoption in an SME in this paper by compiling both steps. This research will contribute to research on ERP in SMEs and practice as guidance for ERP implementors and SMEs in adopting the ERP system